Peran Pemerintah Desa dalam Konsep Perencanaan Pembangunan di Bidang Ekonomi - Bagus, Nanang; Waldus, Frumensius (Yayasan Lentera Avanya Nagari, 2025)
The aim of this research is to find out what the role of the Village Government is in the Development Planning Concept in the Economic Sector of Torongrejo Village as well as the supporting and inhibiting factors in the Development Planning Concept in the Economic Sector of Torongrejo Village. The method used in this research was qualitative with five informants. Data collection techniques used in this research were interviews, observation and documentation. The theory used in this research is the Role Theory from Rivai 2006. The focus of this research is the Government's Role in the Development Planning Process in the Economic Sector of Torongrejo Village. The results of field research show that the Torongrejo village government has played a major role in the concept of development planning in the economic sector, which is implemented according to community aspirations and processed according to applicable laws and regulations. Supporting factors for the role of the Village Government in the Development Planning Concept in the Economic Sector, namely by building a strong business network to support business growth and access to wider markets and strengthening cooperatives as a means of empowering the community's economy to complement each other. each other so that they can create and realize good village economic development planning and can improve community welfare so that they can build a more advanced village. Meanwhile, the inhibiting factors are related to honesty, because economic conditions must be acknowledged with a sense of honesty and an honest nature. In general, people tend to be dishonest about their condition. Tujuan penelitian ini untuk mengetahui apa saja Peran Pemerintah Desa Dalam Konsep Perencanaan Pembangunan di Bidang Ekonomi Desa Torongrejo serta faktor-faktor pendukung dan penghambat dalam Konsep Perencanaan Pembangunan di Bidang Ekonomi Desa Torongrejo. Metode yang dipakai dalam penelitian ini adalah kualitatif dengan jumlah informan lima orang. Teknik pengumpilan data yang digunakan dalam penelitian ini melalui wawancara, observasi dan dokumentasi. Teori yang digunakan dalam penelitian ini adalah Teori Peran dari Rivai 2006. Fokus Peneliitian ini adalah Peran Pemerintah dalam Proses Perancanaan Pembanguan di Bidang Ekonomi Desa Torongrejo. Hasil penelitian menunjukan bahwa pemerintah desa torongrejo telah berperan utama dalam konsep perencanaan pembangunan di bidang ekonomi, yang dilaksanakan sesuai aspirasi masyarakat dan diproses ditetapkan menurut peraturan perundang-undangan yang berlaku. faktor pendukng dari Peran Pemerintah Desa dalam Konsep Perencanaan Pembangunan di Bidang Ekonomi dengan membagun jaringan bisnis yang kuat untuk mendukung pertumbuhan usaha dan akses ke pasar yang lebih luas dan memperkuat koperasi sebagai sarana pemberdaya ekonomi masyarakat agar saling mengisi satu sama lain sehingga dapat menciptakan dan mewujudkan perencanaan pembangunan ekonomi desa yang baik serta bisa meningkatkan kesejahtraan masyarakat sehingga bisa membangun desa yang lebih maju. Sedangkan faktor peenghamat Faktor Penghambatnya yaitu berkaitan dengan kejujuran, karna kondisi ekonomi itu harus diakui dengan rasa jujur dan juga sifat yang jujur. Pada umumnya masyarakat cendrung tidak jujur dengan kondisi dirinya.